The in vitro and in vivo anatomical structure of leaves of Prunus x Davidopersica ‘Piroska’ and Sorbus rotundifolia L. ‘Bükk szépe’ - Kiss, I.; Fábián, M.; Gazdag, Gy.; Jámbor-Benczúr, E.; Ónadi, K. (International Journal of Horticultural Science, 1999)
Immature in vitro leaves showed similar structure of the mesophyll tissue to the immature field-grown (in vivo) leaves of Prunus x davidopersica `Piroska’. Mature leaf anatomical characteristics of in vitro plantlets differ from the field-grown plants. The mesophyll tissue of in vitro plantlets were thinner than the in vivo plants and consisted of only one layer palisade parenchyma, the shape of the cells and the structure of spongy parenchyma basically differed from the field-grown plants. In the case of Sorbus rotundifolia similar anatomical differences were found both in vitro and in vivo as in the case of Prunus x davidopersica `Piroska’.